Interacting force of foreign direct invest (FDI), natural resource and economic growth in determining environmental performance: A nonlinear autoregressive distributed lag (NARDL) approach - (:unkn) unknown (ELSEVIER SCI LTD, 2021)
Considering the strategic position of Algeria both in the global and regional economic complexities through economic liberalization, much has been said about oil shock and economic performance of Algeria but little has been done towards ascertaining the impact of natural resources and foreign direct investment inflow (FDI) on its environmental performance. For this purpose, we adopt Algeria 1970-2018 data to study its sustainable development with focus on its environmental performance. Nonlinear and long run asymmetric cointegration were utilized for a comprehensive research on this topic. Our findings are as follows: positive and negative shocks to the economic growth and fossil fuels on the Algerian environment increases and reduces carbon emission respectively, positive and negative shocks to FDI and natural resources decrease the carbon emission thereby impacting positively on the environment. Hence, pollution halo hypothesis is confirmed for Algeria meaning FDI is impacting positively on the environment and should be encouraged through policy framing and implementation for the case of Algeria.
Keywords: Economic growth; FDI; Natural resources; Sustainability development; NARDL; Algeria; POLLUTION HAVEN HYPOTHESIS; CARBON-DIOXIDE EMISSIONS; ENERGY-CONSUMPTION; CO2 EMISSIONS; UNIT-ROOT; FINANCIAL DEVELOPMENT; TIME-SERIES; TRADE; OUTPUT; DEGRADATION